2011
DOI: 10.1353/cpr.2011.0016
|View full text |Cite
|
Sign up to set email alerts
|

Community-Centered Family Health History: A Customized Approach to Increased Health Communication and Awareness

Abstract: These findings indicate that diverse communities are receptive to FHH intervention, and tailored health educational materials can lead to increased conversations and awareness about health issues across communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…A borderline difference was also noted for provider communication among noncommunicators at baseline. These findings support the results from prior studies examining the impact of family history interventions, which have also reported a positive impact on family communication [28] but not provider communication [21, 22]. …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A borderline difference was also noted for provider communication among noncommunicators at baseline. These findings support the results from prior studies examining the impact of family history interventions, which have also reported a positive impact on family communication [28] but not provider communication [21, 22]. …”
Section: Discussionsupporting
confidence: 89%
“…To date, few studies have examined whether interventions to increase family history awareness and documentation increase the extent to which this information is discussed within families or shared with health care providers [21, 22]. As such, the purpose of this study was twofold.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that examine the translational effect of talking about the family health history to actual practice of preventive behaviors including changing diet, increasing physical activity, and following recommended screening guidelines for personal risk level will be of utmost value to the existing literature. Thus, preventive interventions that target the whole family as a system, where family communication is encouraged, objective risk information is disseminated, communication skills are provided, and a risk-reducing action plan is established will be most successful (O’Leary et al, 2011; Williams, Mullan, & Todem, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Family health history used as a clinical tool can empower the public with a new understanding of health as it relates to their genetic heritage -including the connection between genetics, their family, the inheritance of health and disease, and the influence of environment. Even when theoretical knowledge of genomic science is low, family health history awareness effectively elevates the public’s genomic health literacy because it improves their decision-making skills leading to better personal and family health decisions in the context of everyday situations 30,31 .…”
Section: Discussionmentioning
confidence: 99%